Engaging college and university students effective instructional strategies - Badley, Kenneth Rea 1951- (New York, NY Routledge, 2023)
"Engaging College and University Students outlines creative and effective course organization and teaching-learning strategies for higher education courses. By describing specific instructional best practices, rather than addressing general questions about teaching in higher education, the author presents a valuable resource for educators to consult in the moment. The author explores the challenges of engaging students in online settings and draws comparisons with face-to-face strategies of engagement. By organizing the strategies according to course progress, and offering corresponding rubrics for assessment, this guide for instructors offers a solid foundation for an ever-changing teaching and learning landscape"--
Includes bibliographical references and index.
Keywords: College teaching; Effective teaching; Instructional systems -- Design